Phonology fossilization effect among Arabic native speaker on the acquisition of Malay velar and alveopalatal nasal sound - Abdul Malek, Muhammad Irfan; Ali, Asem Shehadeh Saleh; Al-Dakheel, Mohammad Majed Mojally (International Journal of Social Science and Human Research, 2026)
In learning a second language, speakers usually move between their first language (L1) and the target language (L2). However, the interlanguage process is a transitional linguistic system marked by enduring and resistant errors known as language fossilization is an important stage that is frequently missed. This study examines whether Arabic Native speakers that live in Malaysia acquire novel L2 sounds, the Malay velar nasal \ŋ\ and alveopalatal nasal /ɲ /. Alveolar nasal sound /n/ is a part of both Arabic and Malay inventories while \ŋ\ and /ɲ / sounds which consist of tautosyllabic velar and palatal nasal and glide element are not from Arabic inventory. These crosslinguistic differences present potential difficulty for Arabic speakers due to their phonetic constraints. With these crosslinguistic disparity, this study aims to identify did Arabic native speakers who live in Malaysia facing language fossilization to produce acoustically Malay \ŋ\ and /ɲ / sound or not. Their speech was recorded and analysed using Praat software and measured by formants, duration, and spectrograms of the following vocalic portion as acoustic indices of the Malay \ŋ\ and /ɲ / sound. Findings show that native speakers produce an acoustically distinct Malay sounds of \ŋ\ and /ɲ / due to phonology fossilization from their mother language sound /n/. These findings have significant implications for teaching pronunciation in Malay as a second language, particularly when it comes to dealing with foreign learners’ interlanguage phenomena.